A review of the use of technology to monitor sleep in elite populations - Cole, T. (Journal of Australian Strength and Conditioning, 2017)
Until recently, sleep in elite populations has been taken for granted and poorly controlled. It has since come to light that sleep strategies can be used to enhance areas of performance such as recovery and training adaptation. Similarly, poor or inadequate sleep can be detrimental to performance; affecting aerobic and anaerobic endurance, strength and power, cognitive function and suppressing immune response.